Factors affecting the use of mobile technology in patient-provider communication in hypertensive care in Malawi - Chilongo, Allan (2021)
Evidence suggests that Malawi and other developing countries have benefited a lot through increased adoption of mHealth approaches in service delivery. While the benefits of mHealth are widely published, there lacks a holistic approach in identifying factors that can deter or improve patient-provider communication when using SMS mobile technology in hypertensive care. Objective: Examining factors affecting the use of SMS mobile technology in patient-provider communication in hypertensive care in Malawi. A survey was conducted at Kamuzu Central Hospital and Bwaila Hospital, in the capital of Malawi, Lilongwe. A quantitative approach applying a structured questionnaire was used in this study. A systematic random sampling method was used to obtain its sample of 133 hypertensive patients. A total of 129 participants were interviewed, 89 female (69 %), and with a mean age of 53.2 (SD=8.3). The study has revealed that perception that SMS is a useful tool in communication between the patient and provider (AOR=3.26, 95% CI 1.66 to 6.39), perception that SMS improves quality of care (AOR=5.12, 95% CI 1.57 to 16.71), perception that SMS is easy to use (AOR=4.28, 95% CI 1.35 to 13.50) and perception that the hospital supports the use SMS (AOR=4.11, 95% CI 1.22 to 13.86) were significantly associated with the use of SMS mobile technology. No barrier to the use of SMS among patients in hypertensive care was found. The study has shown that SMS has the potential of improving management of chronic diseases if several factors such as perceived usefulness, perceived ease of use of SMS and social influences are considered when implementing the technology